IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SMK PLUS PELITA NUSANTARA - Dita Pertiwi Supendi; Antonius Alvin Santoso; Dinni Epri Anggraeni; Syifa Maulina; Septia Sundari; Sinta Asna Merys; Huri Suhendri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to describe the implementation of the Deep Learning approach in mathematics learning, determine student responses, and identify obstacles faced in its implementation at SMK Plus Pelita Nusantara. The type used is descriptive qualitative with a case study design. The research subjects involved mathematics teachers, the Principal, and grade XI students of Multimedia (MM) and Computer and Network Engineering (TKJ) Departments. Data were collected through structured observations, semi-structured interviews, and documentation studies, which were then validated using triangulation techniques and analyzed with the Miles and Huberman model. The results of the study show that the Implementation of the Deep Learning Approach on the material of probability has a positive contribution to the quality of learning outcomes and active student involvement. In the Multimedia Department, the highest quality indicator of learning outcomes was achieved in the ability to determine sample spaces and sample points (88.33%). while in the TKJ Department, the highest achievement was in the ability to explain the meaning of probability in everyday life (88.33%). The majority of student responses in both departments showed positive results because learning became more interesting, contextual, and increased self-confidence. However, the implementation of this approach still faces obstacles, including limited curriculum time, disparities in student access to digital technology, and a lack of specific training for teachers in designing exploratory methods. This study concludes that Deep Learning is effective in improving vocational high school students' conceptual understanding of mathematics, but requires school support in the form of ongoing teacher training and optimization of supporting facilities. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan implementasi pendekatan Deep Learning dalam pembelajaran matematika, mengetahui respon siswa, serta mengidentifikasi kendala yang dihadapi dalam penerapannya di SMK Plus Pelita Nusantara. jenis yang digunakan adalah kulitatif deskriptif dengan desai studi kasus, Subjek penelitian melibatkan guru matematika, Kepala Sekolah, serta siswa kelas XI Jurusan Multimedia (MM) dan Teknik Komputer dan Jaringan (TKJ). Data dikumpulkan melalui observasi terstruktur, wawancara semiterstruktur, dan studi dokumentasi, yang kemudian diabsahkan menggunakan teknik triangulasi serta di analisais dengan model Miles dan huberman. Hasil penelitian menunjukan bahwa Implementasi Pendekatan Deeep Learning pada materi peluang memberikan kontribusi positif terhadap kualitas hasil belajar dan keterlibatan aktif siswa. Pada Jurusan Multimedia, indikator kualitas hasil belajar tertinggi dicapai pada kemampuan menentukan ruang sampel dan titik sampel (88,33%). sementara pada Jurusan TKJ, capaian tertinggi berada pada kemampuan menjelaskan pengertian peluang dalam kehidupan sehari - hari(88,33%). respon siswa di kedua jurusan mayoritas menunjukan hasil positif karena pembelajaran menjadi lebih menarik, kontekstual, dan menigkatkan rasa kepercayaan diri. Meski demikian, penerapan pendekatan ini masih menghadapi kendala, antara lain keterbatasan waktu kurikulum, kesenjangan akses teknologi digital dikalangan siswa, serta kurangnya pelatihan khusus bagi guru dalam merancang metode eksploratif. Penelitian ini menyimpulkan bahwa Deep Learning efektif meningkatkan pemahaman konseptual matematika siswa SMK, namun memerlukan dukungan sekolah dalam bentuk pelatihan guru yang berkelanjutan dan optimalisasi fasilitas penunjang.